A Carrier Bag Story of (waste) food, hens and the sharing economy. Issue 1 (2nd January 2018) - Fjalland, Emmy Laura Perez
Abstract: The relationship between food and mobilities is so fundamental that it is easily overlooked, but when you think about it, it is remarkable that cities get fed at all. Food is being produced, transported, bought, stored, sold, cooked, eaten, enjoyed, disposed of and sent into and through bodies, ecologies and different waste, recycling and/or upcycling systems. Within these disposal systems, valuable resources are being lost. Based on empirical work from a Danish project called Sharing City and a local small-scale organic farm (named Hegnsholt), this article elaborates upon how particular waste food from restaurants is a valuable resource for the farm's hens, which, as a result, are so flavoursome that well-known restaurants and cafés purchase their eggs and chickens. This analysis seeks to contribute to discussions on how we are able to respond to environmental change and inspire reparative futures by showing the collaborative, compassionate, responsible qualities of the sharing economy of the exchange of waste food. With the help from The Carrier Bag Theory – an alternative, feminist narrative – and the mobilities paradigm, this article shows the transformative gestures of ethical flavourful food and the value of waste food. This argument is unfolded by looking deeper into the farm as a heterogeneous relational-material entanglement of infrastructures, non-human and human, Nordic food stories, waste, food and feed, diseases and risks and eating and tasting. Based on the food network, this article ought to inspire us to rethink how to share this planet with earth-others.